Art therapy with older adults : a sourcebook - Magniant, Rebecca C. Perry (Charles C. Thomas, 2004)
This book constitutes an important step in demonstrating that art therapy is a unique offering for persons aged sixty-five years and older, giving the potential for enrichment and healing in those lives. Describing the various ways in which art therapy can be used in the treatment of mental and emotional problems of older adults, the editor encourages the reader to use the suggestions and concepts within or tailor them to suit one's own specific working environment or population. Divided into three sections, this book proposes creative art therapies interventions, directives, and ideas along with model programs and examples of work in different settings.